Technological Education and Engineering Pedagogy - D. P. Danilaev; N. N. Malivanov (Russian State Vocational Pedagogical University, 2020)
Introduction. Technological education, being a part of the school curriculum, is presented as a factor and a means of students' socialisation and as "a process and a result of active learning by schoolchildren the general and professional technological culture, general and special ways of technological transformation of reality, and the development of technological competency and creative abilities of a person" 1 . However, over the past decade, the goals of this type of education have undergone several changes: in high-technology competitive world, the priority is given to the development of "universal digital literacy", which affected the content of teachers' work.The peculiarity of a teacher's work in the considered professional and pedagogical activity is the integration of pedagogical, psychological and technicaltechnological components. Currently, there is increased deficit of qualified technology teachers. The modern system of teacher education does not imply fundamental technical training and the training of technical specialists does not require the formation of psychological and pedagogical competencies. The approaches to solve the problem can be drawn from the theory and practical application of vocational pedagogy. Primarily, engineering pedagogy is intended to ensure the quality of personnel of teaching community in engineering institutions.The aim of the present article is to justify the appropriateness of using the methodology of engineering pedagogy in the training of teachers of technological education and the need for expanding of relevant educational programmes in graduate school and in the continuing education system in technical universities.Methodology and research methods. The research was based on the following methodology: the provisions of professionology; systematic analysis of applied aspects of engineering pedagogy; the principle of convergence, defining interdisciplinary and supra-professional relationships, contributes to the design and promotion of the transprofessional nature of actors; the main principle of operation and development of the system of vocational and pedagogical training and advanced training of teachers (including technology teachers) - synchronised content of teaching with scientific, technical and technological innovations.Results and scientific novelty. The authors show the relationship between engineering and technological education goals, based on shared general activity nature. Scientific grounds for the development of engineering pedagogy in terms of training of teachers of technology are identified. The triplicity of such training is demonstrated: the qualification required to be a technology teacher implies possession of effective educational methods, knowledge of child psychology and competences in the field of modern digital technologies and technological equipment. The constantly growing level of knowledge intensity of the latter and the specific intertwining of humanitarian, natural science and applied components in the work of the technology teacher show that the system of his or her continuing education, retraining and advanced training should be organised. On the basis of the technical specialty received earlier, the opportunities of such an organisation, including technical universities, are presented. One effective option could be the development of a digital cluster - a platform, which integrates the resources of educational institutions of different stages, production structures, as well as enterprises of medium and small business. The operation of this cluster will contribute to the rapid spread of modern technologies and it will provide their accessibility and continuity of technological education in school, as well as in secondary vocational and higher education. The common information space will ensure to provide the coordination of instrumental training elements, to compare methods and develop personality-oriented approaches with the help of distance technologies. In addition, the digital cluster can serve as a mechanism for selection and retraining of teachers of universities, technical schools and technology teachers through the formation of a database providing information on mentors with unique competencies.Practical significance. The authors believe that the present research could be useful for the development of alternative methods and forms of training of vocational and pedagogical personnel.